Low complexity rate control for versatile video coding with hybrid Lagrange multiplier - Bukit, Alexander Victor; Suwadi, Suwadi; Wirawan, Wirawan (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Versatile video coding (VVC) has a notable increase in encoding efficiency over high efficiency video coding (HEVC) but bandwidth and storage are limited in real-world video applications, so rate control is crucial. Even if VVC shows a notable increase in encoding capacity over HEVC, the rate control may create fluctuations in video quality and computational complexity. This fluctuation can have a significant impact on the watching experience, particularly in low-bitrate settings. The rate control variables of the consistent resolution and the decreased resolution are proposed in order to make the rate control method hybrid to consistent resolutions and reduce computational complexity. To achieve optimal coding parameters, the frames with varying resolutions Lagrange multiplier (λ), skip coding tree unit (CTU) and quantization parameter (QP) are combined. After evaluation, the average encoding time savings (????????????????????????????) were found to be 19.49%, with a Bjontegaard delta bit rate (BDBR) of -0.44% indicating insignificant quality loss.